Elite sport development in South Korea: An analysis of policy change in the sports of athletics, archery and baseball - Park, J.-W. (2011)
This thesis explores the process of elite sport policy development in South Korea. The thesis analyses the process of policy change in the sports of athletics, archery and baseball at the elite level. The three objectives of the study are: (i) to trace the emergence, development and current status of elite sport policy in South Korea; (ii) to identify how elite sport policy has changed in response to both exogenous factors and endogenous factors; and (iii) to evaluate the utility of the macro-level and meso-level theories of the process of policy change in relation to Korean elite sport development. A multiple-case study approach is adopted, focusing on each of the three sports in turn, wherein a qualitative methodology (semi-structured interviews and document analysis) is utilised in order to elicit data regarding elite sport policy change and development. The analysis of the three case studies is organised by following the two principal themes indentified by Green & Houlihan (2005). Firstly, the organisational structure and administration of the national governing body of athletics is explored followed by an analysis of the nature of the body's relationships with other organisations and an assessment of the influence and significance of business. Secondly, the potential influences on elite sport development in each of the three sports are examined following the three key dimensions of high performance sport policy identified by Green & Houlihan (2005): (i) identification of, and support for, talented athletes; (ii) improvements in sport science, coaching and facilities; and (iii) the provision of more systematic competition opportunities for elite level athletes. It could be argued that Green & Houlihan' (2005) analytical framework was very useful in investigating elite sport development in the cases of athletics, archery and baseball, but it did not identify all distinctive aspect of Korean elite sport system. A further prominent area of elite sport development has emerged and identified in the cases of the three sports: that is a cash-award system. This study reveals the significance of business leaders on the development of the three sports in general, and the sports' successes in international sporting competitions in particular. The study also identifies that all three sports have been shaped by the actions of a sport policy community involving a small number of groups or actors which share common perceptions and the ultimate goal of each sport success in international sporting events. The study concludes that the over-lapping assumptions' between elitism and neo-pluralism are the most likely explanation of the Korean elite sport policy process at the macro-level analysis. It is concluded that although three frameworks, ACF, MSF and policy networks, provide partial insights into Korean elite sport policy process in the three sports, none of the three frameworks adopted provides a comprehensive explanation of policy change in the three sports. In particular, the advocacy coalition framework has proved useful in drawing attention to the notion of exogenous factors (e.g. a sport's failure at an international sporting completion and the change of the presidency of NGBs) and policy learning as a key source of policy change. The concept of policy community which is a type of policy network has provided partial insights in terms of illuminating the characteristics of the Korean elite sport policy process at the macro-level analysis, although it has not been a particularly useful lens for explaining the mechanism of policy change in the three sports investigated.